IMPLEMENTATION OF NUSANTARA ISLAMIC VALUES THROUGH EXTRACURRICULAR ACTIVITIES IN ISLAMIC EDUCATIONAL INSTITUTIONS - Haniyah, Haniyah; Amrela, Umah (FORPIM PTKIS ZONA TAPAL KUDA, 2024)
The large number of deviant behavior of students and teenagers which is not in accordance with religious norms, Pancasila norms and the noble values of Indonesian culture has prompted various parties to question the effectiveness of the implementation of religious education in schools. Seeing these problems, it is necessary to have several breakthroughs that can be made in cultivating religious and social character with an Islamic archipelago pattern from an early age which is implemented in schools both through classroom learning and other activities such as religious extracurriculars. Nusantara Islamic education is an internalization process in the form of transferring the values of Islamic religious methods that are characterized by the culture of Muslim communities in the Indonesian archipelago. Initially, this style was exemplified by the spreaders of Islam in Indonesia, namely the Wali Songo, especially in Java, through various paths and methods, including through education, although with traditionalist methods, namely the culture and cultural approach of the local community by incorporating religious values into the habits of previous communities. , until this education was developed from generation to generation until today. This article was written by tracing the history of the legacy of Islamic culture and culture in the archipelago which continues to be maintained and developed in such a way in extra activities carried out at the Islamic boarding school-based Plus Darus Sholah Middle School educational unit as a form of inheritance of the Islamic da'wah method in the archipelago in teaching and practicing the teachings of the Islamic religion. . The focus of the problem in this research is: 1) How is the implementation of Indonesian Islamic education at SMP Plus Darus Sholah?, and 2) What extra activities are chosen as part of Islamic Archipelago education at SMP Plus Darus Sholah Jember? This research is qualitative research with a descriptive approach using observation, interviews and documentation studies.